Analisis Keputusan Konsumen: Kesadaran Merek, Kualitas Produk, dan Strategi Penetapan Harga Bisnis Syariah - Putri, Novita Nadiya; Sisdianto, Ersi; Susanti, Yeni (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the impact of brand awareness, product quality, and pricing strategy on consumer purchasing decisions at Outlet Binaan Aksesmu (OBA) Stock Point in Tanjung Senang, Bandar Lampung. It also explores how Islamic business ethics enhance these factors, providing insights for OBA to align policies with Islamic principles of balanced effort and trust (tawakal). Research Methodology: A quantitative survey method was employed, with data collected from 530 OBA Stock Point outlets in Tanjung Senang. Accidental sampling was used, selecting respondents based on accessibility. Data were analyzed using Partial Least Squares (PLS) version 3.2. Results – Brand awareness, product quality, and pricing strategy significantly and positively influence consumer purchasing decisions at OBA Stock Point. Conclusions: The study confirms the importance of these three factors in shaping consumer choices while highlighting the reinforcing role of Islamic business ethics. Limitations: Findings are based on self-reported survey data, which may reflect subjective biases. The study’s scope is limited to one location, reducing generalizability. Data quality may also be influenced by external constraints, such as time limitations during questionnaire completion. Contribution: This research uniquely integrates Islamic ethical values into consumer behavior analysis, offering theoretical and practical insights for businesses operating within Islamic frameworks. It advances academic discourse while guiding policy development for faith-based marketing strategies.